High-resolution dating of granite petrogenesis and deformation in a lower crustal shear zone: Athabasca granulite terrane, Western Canadian Shield - Dumond, G; McLean, N; Williams, ML; Jercinovic, MJ; Bowring, SA (SelectedWorks, 2008)
The Athabasca granulite terrane represents > 20,000 km2 of continental lower crust exposed in the hanging wall of the ca. 1.85 Ga thrust-sense Legs Lake shear zone in the western Canadian Shield. The terrane and the thrust zone are cut by the Grease River shear zone. The structure hosts a syn-tectonic granite dike with a high-precision ID-TIMS zircon 207Pb/206Pb crystallization age of 1922.6 ± 0.4 Ma (MSWD = 3.1, 2[sigma]). Detailed textural analysis and in situ electron probe microanalysis (EPMA) of monazite in the dike indicate three discrete episodes of strain accumulation, each corresponding to syn-kinematic growth of monazite. The results provide evidence for a previously unrecognized > 100 m.y. episodic record of sub-horizontal NW-SE shortening and dextral shear strain along the Grease River shear zone. High-Ca domains in ca. 1.92-1.90 Ga monazite are linked to protracted high-T strain (ca. 650-700 °C) at lower crustal depths (ca. 1.0 GPa) and correlated with indentation of the Slave craton along the Great Slave Lake shear zone. Syn-kinematic overgrowths of low-Ca monazite + apatite are interpreted as products of deformation-enhanced dissolution and re-precipitation of monazite at 1846 ± 9 Ma (MSWD = 1.1, 2[sigma]). The third generation of syn-kinematic monazite yield ca. 1.8 Ga ages. The dataset constrains, for the first time, coeval movement along the strike-slip Grease River shear zone and the thrust-sense Legs Lake shear zone during ca. 1.85 Ga dextral transpression and uplift of continental lower crust to middle crustal levels (ca. 0.5 GPa). Circa 1.8 Ga syn-kinematic monazite domains in dynamically recrystallized feldspars support brittle-ductile reactivation along the Grease River shear zone at shallower crustal levels, coincident with intra-continental strike-slip strain during culmination of the Trans-Hudson orogeny.